Severe Pneumonia Caused by Infection With Tropheryma whipplei Complicated With Acinetobacter baumannii Infection: A Case Report Involving a Young Woman - Wang, Sheng; Xia, Demeng; Wu, Jianghong; Jia, Dandan; Li, Lei; Xu, Shuogui (Frontiers in Public Health, 2021)
Whipple’s disease is a very rare systemic infectious disease, and very few cases have been reported. However, it can be fatal if not diagnosed and treated appropriately. The major clinical manifestations of this disease are usually digestive and nervous system symptoms. The majority of patients are male and between 40 and 50 years old. Although respiratory symptoms of this disease have rarely been reported, they pose a serious threat to the lives of the patients, especially when they progress to severe pneumonia. During admission to the hospital, Acinetobacter baumannii infection makes treatment more difficult. While most patients are middle-aged men, more attention should be given to the diagnosis and treatment of affected young women. To our knowledge, the case presented in the study is the first case of Tropheryma whipplei infection that resulted in severe pneumonia and was complicated by A. baumannii infection during treatment. We hope that our study can serve as a reference for the diagnosis and treatment of related cases in the future.